Respostas

2014-05-20T10:27:15-03:00
                               b²-4.a.c
                               (-7)²-4.1.10
                                 49-4.10
                                  49-40
                                     9

           -b+-raiz de 9:2
            7+3

                              x1=5
                              x2=2

a=1
b=-7
c=10

2014-05-20T10:32:07-03:00
x²-7x+10=0

x = - b + - 
√b² - 4.a.c
              2.a
x = - (-7) + - √(-7)² - 4.1.10
              2.1
x = + 7 + - √49 -40
              2
x = 7 + - √9
        2
x = 7 +- 3
         2
x' = 7 + 3 = 10   -----> x' = 5
        2          2
x" = 7 - 3  4   -----> x" = 2
        2         2

Resposta (x',x") = (5,2)